Hazard rating of substances systems developed by NIOSH's RTECS-NOHS and USEPA - Law, Puong Ling, Dr.; Ellenbecker, Michael J.; Ng, Chee Khoon, Ir. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/